Statelessness and the rights of Children in Kenya and South Africa: A Human Rights Perspective - Sutton, Nikeeta Louise Joan (University of the Western Cape, 2019)
Magister Legum - LLM === Stateless children and those at risk of becoming stateless has been an ongoing issue both on a domestic level as well as internationally. In many African countries children face discriminatory and arbitrary nationality laws as a result of which they are not registered and granted citizenship in their country of birth or where they are found or undocumented. Thus, children continue to be stateless and will not be able to register their own children once they become parents. As a result, this creates an issue of transgenerational statelessness which will continue indefinitely and as such, requires attention and action both on a domestic and international level as a matter of urgency. While laws have been enacted in the aim to protect stateless children or children at risk of becoming stateless, the lack of guidelines in the implementation thereof creates a difficulty for children to acquire a nationality. States in this regard have the responsibility to create mechanisms to facilitate the implementation of laws especially when dealing with vulnerable groups such as stateless children.